STRATIGRAPHY AND PALEOGEOGRAPHY OF MARINE HOLOCENE (THE PRIMOR'E SHELF) - Kuz'mina N.N.; Taldenkova E.E. (My University, 2000)
Representative materials from sea drilling sites with complete geological records and detailed geological-geomorphological analysis of sediments in the Primor'e coast and shelf (lithological and paleontological methods combined with radiological dating) enabled stratigraphic subdivision and correlation of these sediments and reconstruction of Holocene paleogeographic events. Most significant environmental changes occurred in the initial Holocene time (10.3-10.0 ka ago) and at the beginning of the Boreal period (about 9 ka ago). The corresponding stratigraphic levels are marked by significant changes in lithology and compositions of palynological and diatom assemblages in response to climatic and sea-level fluctuations. Three thermal maximums: Boreal, Atlantic (optimum) and Subboreal, are distinguished in the Holocene.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен